2018
DOI: 10.1016/j.bja.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of prothrombin complex concentrate for management of coagulopathy after cardiac surgery: a propensity score matched comparison to plasma

Abstract: Our exploratory study suggests that the use of PCCs as part of a multifaceted coagulation management strategy may have blood-sparing effects. Their incorporation into clinical practice, however, must await determination of their risk-benefit profile via multicentre randomised trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…Fitzgerald et al retrospectively reviewed patients who received PCCs undergoing cardiac surgery with CPB in a propensity score matched comparison with those who received FFP and found that the odds ratio for red cell avoidance was 2.4 (95% CI: 0.24-1.03) for the PCC group. 51 Those who received PCCs also had lower incidence of massive transfusion and refractory bleeding.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…Fitzgerald et al retrospectively reviewed patients who received PCCs undergoing cardiac surgery with CPB in a propensity score matched comparison with those who received FFP and found that the odds ratio for red cell avoidance was 2.4 (95% CI: 0.24-1.03) for the PCC group. 51 Those who received PCCs also had lower incidence of massive transfusion and refractory bleeding.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…[97][98][99] In patients requiring urgent operations, reversal of vitamin K antagonists was more effective with prothrombin complex concentrates (PCC) compared with FFP, mainly because of a more rapid hemostatic effect. 100 Several studies [101][102][103][104] have reported that administration of PCC is also more effective than FFP in CPB-related coagulopathic bleeding and leads to decreased postoperative bleeding and transfusion. However, concerns regarding increased risk for postoperative acute kidney injury have been raised in one study.…”
Section: Rbc Transfusion and Use Of Cell Salvagementioning
confidence: 99%
“…It should be noted that this is also true for traditional blood components, such as platelets and plasma. There is growing evidence showing the benefits of PCCs for patients with decreased thrombin generation outside of VKA reversal, such as in cardiac surgery . In contrast, in the United States, the available four‐factor PCC is exclusively approved for urgent reversal of VKA therapy, not other acquired deficiencies …”
Section: Pccsmentioning
confidence: 99%
“…There is growing evidence showing the benefits of PCCs for patients with decreased thrombin generation outside of VKA reversal, such as in cardiac surgery. 12 In contrast, in the United States, the available four-factor PCC is exclusively approved for urgent reversal of VKA therapy, not other acquired deficiencies. 13 The major risks of PCCs are thromboembolic complications due to overcorrection of thrombin generation, which in principle is related to the ratio of FII (prothrombin) to antithrombin.…”
Section: Pccsmentioning
confidence: 99%